Upconversion manipulation by local electromagnetic field. (December 2017) - Xu, Wen; Chen, Xu; Song, Hongwei
Highlights: The generation principle and interaction rules of localized electromagnetic field induced upconversion enhancement. Experimental progresses of upconversion enhancement induced by metal/semiconductor plasmon, and photonic crystal effect. Various applications developed by local field enhanced upconversion. Graphical abstract: Abstract: Rare earth doped upconversion nanocrystals (RE-UCNCs) have attracted extensive interests owing to their unique physical properties and great potential applications in bio-application, photonic and photoelectric devices etc. Although UCNCs open doors to a wide range of new opportunities, they are confronting with some difficulties and one of the fatal problems is their low upconvsersion luminescent strength/efficiency. To date, various methods have been explored to solving this significant issue. Totally to say, the methods can be classified into two aspects, the traditional size, structure, surface and crystal field controls of the UCNCs, and the novel local electromagnetic field modulation surrounding the UCNCs. The local electromagnetic field modulation on UCNCs is a powerful strategy to enhance the strength/efficiency of UCNCs, reporting enhancement from several times up to four orders in short times. The timely and concise summary on the previous literatures is significant for more rapid and formulated development of this field. This review is aimed at offering a comprehensive framework for metal/semiconductor plasmon-induced and photonic crystal effect induced upconversion enhancement. Differing from the other review articles, we first introduced the generation principle of localized electromagnetic field in metal/semiconductor nanostructure/photonic crystals, and their general interaction rules with various emitters. Then, we summed up the recent published works on the local field modulation-induced upconversion enhancement, on emphasis we did our best to discover the generality of obtaining highly improved photoluminescence for any emitters and the personality of realizing highly improved upconversion enhancement. We further prospected the future development in this attractive field based on the previous theoretical and experimental results and the requirement of application. The marriage of upconversion with nanophotonic could explore a novel frontier in photonics that potentially spawn many exciting new fields.